Amphorae from the barracks of Legio VIII Augusta and Legio I Italica in Novae - Dyczek, Piotr (Rei Cretariae Romanae Fautorum Acta, 2017)
The Lower Danubian fortress of Novae is known foremost as the seat of the Legio I Italica, but its history was somewhat more complicated. First, the Legio VIII Augusta arrived from Poetovio in AD 44 and built the first timber-and-earth fort. Excavations, despite continuing for more than half a century, had yielded little palpable evidence of the presence of this legion: only some traces of the timber-and-earth fortifications and remains of wooden architecture. In 2011, a new sector was opened (XII), encompassing the part of the fort where the barracks of the first cohort were to be expected. The results provided a more inclusive picture of the military presence of Roman legions in the fortress of Novae. Extensive later rebuilding, various conflagrations, earthquakes and large-scale earthworks wrought havoc with structures raised by legionaries from the VIII Augusta, hence the discovery of a large army barrack in the new sector came as somewhat of a surprise. It had the characteristic layout and size of an army barrack and hence should be interpreted as the living quarters of the first cohort. The full width of the barrack turned out to be 16 m. Six full contubernia were also cleared, as well as porticoes lining the barrack on two sides. It is clear now that the barrack was rebuilt at some point, but the work was limited to a different arrangement of interior partition walls. In AD 69 the VIII Augusta was replaced with the I Italica brought from Gaul. The new legionaries rebuilt the fortress in stone, including the army barracks. Extensive later construction works in the area have obliterated to some degree the plan of this building and more excavations are necessary before there is clarity as to its layout.